Occurrence of circulating immune complexes in beta-thalassaemia major. Issue 2 (February 1978) - Casali, P; Borzini, P; Vergani, D; Mieli-Vergani, G; Masera, G; Zanussi, C
Abstract : The presence of circulating soluble immune complexes and the level of complement were investigated in sera from 21 patients with beta-thalassaemia major, including both splenectomised and nonsplenectomised patients. A high level of immune complexes was found in half of these cases. Reduced complement levels were seen less frequently. There was no correlation between the presence of circulating immune complexes, decreased complement levels, and thpresence or absence of the spleen. The level of immune complexes increased with the age ofthe individual, i.e. with the duration of the disease.